Case Report: Circulating Tumor Cells as a Response Biomarker in ALK-Positive Metastatic Inflammatory Myofibroblastic Tumor - Bonvini, Paolo; Rossi, Elisabetta; Zin, Angelica; Manicone, Mariangela; Vidotto, Riccardo; Facchinetti, Antonella; Tombolan, Lucia; Affinita, Maria Carmen; Santoro, Luisa; Zamarchi, Rita; Bisogno, Gianni (Frontiers in Pediatrics, 2021)
Inflammatory myofibroblastic tumors (IMTs) are locally aggressive malignancies occurring at various sites. Surgery is the mainstay of treatment and prognosis is generally good. For children with unresectable or metastatic tumors, however, outcome is particularly severe, limited also by the lack of predictive biomarkers of therapy efficacy and disease progression. Blood represents a minimally invasive source of cancer biomarkers for real-time assessment of tumor growth, particularly when it involves the analysis of circulating tumor cells (CTC). As CTCs potentially represent disseminated disease, their detection in the blood correlates with the presence of metastatic lesions and may reflect tumor response to treatment. Herein, we present a case report of a 19-year-old boy with an ALK-positive IMT of the bladder, proximal osteolytic and multiple bilateral lung lesions, who received ALK inhibitor entrectinib postoperatively and underwent longitudinal CTC analysis during treatment. Antitumor activity of entrectinib was demonstrated and was accompanied by regression of lung lesions, elimination of CTCs from the blood and no development of relapses afterwards. Therapy continued without any clinical sign of progression and 24 months since the initiation of treatment the patient remains symptom-free and disease-free